(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Urban waste management presents still major difficulties, especially in fast-growing cities like Kampala. This paper looks at how using digital technologies might help rural-urban communities better manage their waste. Data came from secondary sources, field observations, and questionnaires. With 60% of issues still unresolved, Kampala City struggles greatly with waste management. Just 28,000 tons of municipal garbage find their way to landfills every month, or only 40% of all created waste. The waste situation in Kampala has gotten rather bad. Previously managing 1,400 to 1,700 tons of waste daily, Kiteezi landfill, the main disposal site for the city, exceeded its capacity since 2009 and collapsed in 2024, with 64% efficiency, the waste collecting system lets most of the trash go unharmed. For locals, this poses serious health hazards as well as environmental ones. Given Africa's urban population is predicted to rise from 470 million in 2015 to 1.2 billion by 2025, the scenario could get more difficult. This study will explore how digital technologies might transform waste management in Kampala City. To address mounting urban waste issues, smart solutions including loT-enabled recycling bins and mobile apps now link homeowners with collectors. We will discuss how artificial intelligence can be used in recycling centers, how block chains provide waste handling transparency, and how data analytics might forecast waste trends to help to allocate resources more effectively. Results point to low waste collecting frequency, high organic waste composition, and inadequate recycling programs. Modern ideas come from digital technologies including smart bins, GIS tracking, and mobile waste collecting apps. Proposed to maximize operations is an integrated solid waste management model. The findings of this study end with suggestions for community involvement techniques and digital infrastructure acceptance.